Redox status and antioxidant response in professional cyclists during training - Leonardo-Mendonca, R. C.; Concepcion-Huertas, M.; Guerra-Hernandez, E.; Zabala, M.; Escames, G.; Acuna-Castroviejo, D. (European Journal of Sport Science, 2014)
The aim of this study was to investigate whether different phases of training affect oxidative stress and antioxidant defences in professional cyclists. Ten professional cyclists, aged 21.8 ± 2.5 years, were enrolled in the study. They were classified into two groups of five athletes each one with similar nutritional intake excepting for the overload of vitamin C (1000 mg day-1) and E (400 mg day-1) supplementation in one of them. The cyclists of both groups performed the same exercise design, consisting of hard, tapering and recovery training periods. Total antioxidant capacity (TAC) of the diet, plasma oxygen radical absorption capacity (ORAC), lipid peroxidation (LPO), DNA damage (8-OHdG) and erythrocyte glutathione disulfide/glutathione ratio (GSSG:GSH-1) were measured. During the intense exercise trainings, the cyclists without vitamin supplements had the TAC of diet significantly lower than the supplemented group. Plasma ORAC, LPO and 8-OHdG were similar in both groups of athletes. Athletes with supplements had a basal LPO:ORAC-1 ratio lower than that without supplements, but this ratio converged to the same level at the end of the training in both groups of cyclists. Both groups of cyclists showed similar changes in GSSG:GSH-1 ratio and in GSSG and GSH levels along the study. The data suggest that well-trained athletes with suitable ultra-endurance training volume and intensity do not require antioxidant vitamin supplements to adapt their endogenous antioxidant defenses to exercise-induced ROS.